Gazing behavior during mixed-sex interactions: Sex and attractiveness effects - Van Straaten, Ischa; Holland, Rob W.; Finkenauer, Catrin; Hollenstein, Tom; Engels, Rutger C.M.E. (Springer New York, 2010)
We investigated to what extent the length of people's gazes during conversations with opposite-sex persons is affected by the physical attractiveness of the partner. Single participants (N = 115) conversed for 5 min with confederates who were rated either as low or high on physical attractiveness. From a mating strategy perspective, we hypothesized that men's increased dating desire towards highly attractive confederates would lead to longer periods of gazing, whereas women's gazing would be less influenced by their dating desire towards highly attractive confederates. Results confirmed our hypothesis, with significantly increased gazing for men in the high attractiveness condition but no significant differences in women in the two attractiveness conditions. Contrary to past research findings, there was no significant sex difference in the size of the effect of physical attractiveness on dating desire. The results were discussed in terms of preference for physically attractive partners and communication strategies during courtship.
Keywords: Dyadic interaction; Gazing; Physical attractiveness; Sex differences; Arts and Humanities (miscellaneous); General Psychology